Improving the security of LBlock lightweight algorithm using bit permutation - AlDabbagh, Sufyan Salim Mahmood; Alshaikhli, Imad Fakhri Taha (2013)
Lightweight block cipher algorithms are important for constrained environment. LBlock uses word permutation to do the diffusion while this research uses bit permutation to increase the number of active Substitution box (S-box). The number of active S-box is a regular method to evaluate the security against linear and differential attacks. The bit permutation method is described in this research with analysis and discussion. The preliminary results show that the proposed algorithm has 32 active S-box for 13 rounds which is higher than 32 active S-box for 15 rounds of LBlock algorithm. Also, we can conclude that the proposed algorithm is better than LBlock algorithm in the perspective of security.